SOSIALISASI PERAN SIA DAN TEKNOLOGI INFORMASI DAN SDM PENGELOLA BUMDES - Putri, Sara Ayudia; Hertati, Lesi; Terrtiavini, Terrtiavini; Heryati, Agustina; Cahyani, Nani; Puspitawati, Lilis (Transpublika Publisher, 2024)
This community service aims to introduce the role of AIS and IT and increase the capacity of human resources of BUMDes managers. BUMDes are important in driving the village economy, but often experience constraints in efficient financial and operational management. Effective implementation of AIS and IT can help overcome these obstacles, but requires adequate understanding and HR skills. This activity involves intensive training and mentoring to BUMDes managers. The method used is a participatory approach with workshops, seminars, and practical training sessions. Data was collected through observation, questionnaires, and interviews to assess the effectiveness of the program. The results show an improved understanding and skills in using AIS and IT to support BUMDes management. They are better able to implement an integrated accounting system and utilize IT to improve operational efficiency and financial transparency. The program also identified challenges, such as limited technology infrastructure in the villages and the need for ongoing support.